Audio Visual aids in Medical teaching: Are they being over Subscribed? - Mishra, S.M. (Journal of Nepalgunj Medical College, 2018)
In the ancient past the teaching was quintessentially verbal. The Students had to be “Shrutidhar”(remembering by listening to the teachers). Our ancient Scriptures are a witness to this. Since then, much water has flown under the bridge. We now live in a time where an effective communication has not only to be verbal but visual as well. The controlled trials have unequivocally shown that verbal presentations beefed-up with visual supplements make such presentations more informative, interesting and intensify cognitive learning. For this, the cutting-edge technology and tools like PowerPoint presentations and OHPS have opened new vistas and dimensions in teaching methods. The poor black-board and chalk have been given a cold valediction. However, wisdom always demands a re-assessment of the usefulness of the newly invented tools. Are these visual aids making the teaching more immersive and interactive? Are these aids being used in proper perspectives? The answer will be a flat “no” if a student is asked to answer honestly. A large majority of the teachers are using this aid for their convenience not to increase the students cognitive engagement in the class. Transparencies of OHPS howsoever transparent they might be yet, they create a barrier between the students and teacher. The PowerPoint Presentations are more often too numerous and contain too much information that student can digest. A monotonous recital of these makes the students totally disinterested in the lecture. They feel that teacher is reciting from the lines taken down from the books. I think there is still a place for black-board and the newer invaluable teaching aids should be very subtlety used and used in proper perspective. Prof. S.M. Mishra MS (Surgery), MS (Ortho), FRCS Editor In Chief